A row-by-row axial turbine process model based on a one-dimensional thermofluid network approach - Pottas, Roelof J H (Department of Mechanical Engineering, 2017)
A detailed turbine process model has been developed, based on a stage-by-stage discretisation using 1D flow elements. The complete turbine is represented by these flow elements in which the fundamental mass, energy and momentum conservation equations for compressible flow through 1D "stationary channels" and 1D "rotating channels" were solved. The required closure relations were obtained from the various loss coefficients for turbine stators, rotors and leakage flows which were characterised using correlations available in the literature. Several of the commonly applied loss calculation methods were investigated. A test case of a real turbine obtained in the literature was used to validate the model. Three models with different discretisation schemes were tested. In each of these schemes the stator and rotor flow passages were represented by a different number of elements along the radial direction. A number of hypothetical anomalies that often occur in industrial turbines were applied to the test case to demonstrate how the modelling approach can be applied in practice. The model agrees well with the test data for the nominal case and several of the off-design cases. For the nominal case the maximum deviation in total pressure of <2% occurs after the first stage and there is little variation between the results obtained with the three different models. The total enthalpy values are predicted within an accuracy of <1%, again with similar results obtained by the three different models. All three models predict the efficiency well for a broad range of relative mass flow rates. A slight improvement in the prediction of losses is observed in the models that use more elements to represent each stator and rotor passage.